A ratio-cum-regression estimator of population mean in unequal probability sampling design. Issue 2 (1st February 2020) - Khan, Hina; Gupta, Sat; Farhat, Habiba
Abstract: A new ratio-cum-regression type estimator of population mean is proposed in unequal probability sampling design. Its mean square error, up to first-order approximation is derived. A simulation study is carried out to compare the performance of the proposed estimator with some existing estimators.